Aphanius kruppi, a new killifish from Oman with comments on the A. dispar species group (Cyprinodontiformes: Aphaniidae) - Freyhof, Jörg; Weissenbacher, Anton; Geiger, Matthias (Zootaxa, 2017)
Eight species are recognised in the Aphanius dispar group. Aphanius dispar from the Red and Mediterranean Sea basins, A. stoliczkanus from coastal areas of the Arabian/Persian Gulf, the northern Arabian Sea east to Gujarat in India, the Gulf of Oman and some endorheic basins in Iran and Pakistan, A. richardsoni from springs in the Dead Sea basin in Jordan and Israel, A. sirhani from the Azraq Oasis in Jordan, A. ginaonis from one spring in Iran, A. furcatus from few streams and springs in Iran and A. stiassnyae from one lake in Ethiopia. Aphanius kruppi, new species, from the Wadi al Batha drainage in northern Oman, is distinguished from adjacent A. stoliczkanus by having 9–14 brown or grey lateral bars on the flank in the male, a roundish, diamond-shaped or somewhat vertically-elongate blotch centred on the caudal-fin base in the female and 2–3 scale rows on the caudal-fin base. The available molecular genetic data for A. dispar reject the hypothesis of the presence of a single widespread coastal species in the Middle East and make it likely that two additional unidentified species occur in the Red Sea basin.